Alginate-Encapsulated Gd-Ni Catalysts For Photocatalytic Degradation Of Theophylline In Aqueous Solution - Norezatul Shahirah, Ahmad Zamanhuri; Norzahir, Sapawe; Muhammad Farhan, Hanafi; Diyana Faziha, Mohamad; Siti Fatimah, Ibrahim; Lusi, Ernawati; Bernard, Maringgal; Daniel Joe, Dailin (Integrated Publishing Association, 2025)
Pharmaceutical pollutants, including theophylline, a prevalent xanthine-based drug, present significant risks to aquatic ecosystems owing to their persistence and resistance to standard wastewater treatment methods. This study presents the synthesis of a novel gadolinium (Gd) and nickel (Ni) co-doped alginate bead catalyst through in situ co-precipitation and sol-gel techniques, with the objective of improving the photocatalytic degradation efficiency of theophylline in aqueous media. The Gd-Ni nanoparticles were effectively immobilized in alginate matrices, resulting in stable, magnetically separable beads that exhibit enhanced surface area and light absorption characteristics. Batch experiments were performed to evaluate the effects of critical operational parameters such as pH, catalyst dosage, and initial theophylline concentration on degradation performance under visible light irradiation. The optimized 7% Gd-doped Ni-alginate catalyst demonstrated an 84% removal efficiency within 240 minutes, showing enhanced activity relative to non-doped and single-metal-doped alternatives. The photocatalyst exhibited satisfactory reusability across three cycles, showing minimal activity loss. The findings suggest that Gd-Ni nanoparticle-embedded beads may serve as effective and sustainable photocatalysts for the removal of pharmaceutical contaminants from water.